Access-Based Services for the Base of the Pyramid. (November 2018) - Schaefers, Tobias; Moser, Roger; Narayanamurthy, Gopalakrishnan
One key challenge for consumers at the base of the pyramid (BoP) is access to products that could transform their livelihood, leading to nonconsumption as the dominant pattern. Previous studies have claimed that nonconsumption could be addressed with services offering access to goods without ownership. Drawing on expected utility theory, we conduct two experimental studies in rural India that provide the first empirical support for the idea that the availability of access-based services reduces nonconsumption at the BoP. Additionally, we show that this effect is explained by BoP consumers' expected utility assessment as reflected in their perception of access being more affordable and entailing less financial risk than ownership. We also demonstrate that access temporality, an important configurational variable for access-based service providers, affects the degree to which nonconsumption can be decreased. Compared to short-term access, BoP consumers perceive long-term access to be too similar to ownership in terms of affordability and financial risk, which causes them to refrain from purchasing. Overall, the results suggest that access-based services represent a viable alternative for addressing nonconsumption at the BoP. However, service providers should be aware that short-term access is required to gain acceptance among BoP consumers.